KOMPILASI HUKUM ISLAM SEBAGAI HUKUM MATERIIL PADA PERADILAN AGAMA - Dadang Hermawan; Sumardjo Sumardjo (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2015)
As the biggest Muslim country and a state law, it is only natural if Islamic law is used as a source of reference in the formation of national laws. In the history of the development of Islamic law in Indonesia, Islamic law was merely based on fatwa of Islamic scholars and their interpretation. Major breakthrough occurred in the New Order Era with the issuance of Presidential Degree No 1/1991 on the Compilation of Islamic Law (KHI) on Jun 10, 1991. The Decree was then followed by the Decision of Minister of Religious Affairs No 154/1991 on the implementation of Presidential Decree No 1/1991 regarding the dissemination of KHI as a suplement for the Law No 7/1989 on Religious Court. KHI has filled the empy seat of material law in Religious Court. It provides judges of Religious Court with materials to observe and decide on cases. It may also eliminate debates among judges on the problem of inheritance marriage and endowment (waqf). Although KHI is far from perfection, it may be used as material sources for religious court and there is no religious court decision which left KHI out.